Brain Routes for Reading in Adults with and without Autism: EMEG Evidence - Moseley, Rachel L. (Springer US, 2013)
Reading utilises at least two neural pathways. The temporal lexical route visually maps whole words to their lexical entries, whilst the nonlexical route decodes words phonologically via parietal cortex. Readers typically employ the lexical route for familiar words, but poor comprehension plus precocity at mechanically ‘sounding out’ words suggests that differences might exist in autism. Combined MEG/EEG recordings of adults with autistic spectrum conditions (ASC) and controls while reading revealed preferential recruitment of temporal areas in controls and additional parietal recruitment in ASC. Furthermore, a lack of differences between semantic word categories was consistent with previous suggestion that people with ASC may lack a ‘default’ lexical-semantic processing mode. These results are discussed with reference to dual-route models of reading. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10803-013-1858-z) contains supplementary material, which is available to authorized users.